2018
DOI: 10.1503/cmaj.180013
|View full text |Cite
|
Sign up to set email alerts
|

The evolving epidemiology of Clostridium difficile infection in Canadian hospitals during a postepidemic period (2009–2015)

Abstract: Rates of health care-associated infection have decreased across Canada. In nonepidemic settings, NAP4 has emerged as a common strain type, but NAP1, although decreasing, continues to be the predominant circulating strain and remains significantly associated with higher attributable mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 20 publications
7
45
0
2
Order By: Relevance
“…In addition, prevalence of health care-associated infections among patients in the ICU markedly declined. These results are consistent with other CNISP data, 11,20 which suggests improvements in the prevention of health care-associated infections in Canadian acute care hospitals. This trend has occurred despite some changes in hospital patient populations that would be expected to increase infection risk, such as a higher proportion of patients in the ICU.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, prevalence of health care-associated infections among patients in the ICU markedly declined. These results are consistent with other CNISP data, 11,20 which suggests improvements in the prevention of health care-associated infections in Canadian acute care hospitals. This trend has occurred despite some changes in hospital patient populations that would be expected to increase infection risk, such as a higher proportion of patients in the ICU.…”
Section: Discussionsupporting
confidence: 92%
“…(CNISP) provides data on the incidence of selected health careassociated infections and antimicrobial resistant organisms [11][12][13][14][15] and conducted point-prevalence surveys in 2002 and 2009. 16,17 In 2017, we replicated a point-prevalence survey in CNISP hospitals, to provide an up-to-date estimate of the burden of health careassociated infections and antimicrobial-resistant organisms causing these infections in Canadian hospitals, and to describe the trends observed over time in the 3 surveys.…”
mentioning
confidence: 99%
“…Further study is needed to fully understand the effects of reductions in fluoroquinolone use in CNISP hospitals where there has been a concurrent reduction in the rates of hospital-associated MRSA and CDI. Notably, over the surveillance period, there was a reduction in CDI caused by strain type NAP1 (associated with ribotype 027 and highly fluoroquinolone resistant) at CNISP hospitals [22]. Reductions in CDI infections have been associated with decreased fluoroquinolone use in Canada [21], the United Kingdom [23], and the United States [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Ribotyping surveillance data has shown that the molecular epidemiology of the disease is shifting. The prevalence of the epidemic ribotype 027 is decreasing globally, while ribotypes 106 and 017 have become the most common strains in Europe and Asia, respectively [10][11][12][13][14][15]. The most recent national data provided by the Centers for Disease and Control (CDC) shows similar trends in the US, however, this data is derived from 1000 to 1500 annual samples submitted from ten states, not including Texas [13].…”
Section: Introductionmentioning
confidence: 99%